Hip fracture as the tracer condition - Kassim Javaid, M; Chana, J; Cooper, C (Bailliere Tindall Ltd, 2013)
Hip fractures represent the most severe complication of osteoporosis from the perspectives of the patient, carer, health care system and society. Given the strong association with age, numbers are set to rise significantly in the next few decades despite evidence that the age adjusted rates in some countries are either plateauing or falling. Given the almost invariable need for inpatient admission, hospital administrative data for hip fractures remain a robust measure of number of hip fractures in the community and can be extrapolated to determine the total expected number of clinical fragility fractures from the same population. Both process and outcome standards have now been developed to benchmark clinical quality in the care of patients with hip fractures and fragility fractures at other sites. © 2014 Elsevier Ltd. All rights reserved.